Caring Behaviors for the Elderly in Primary Health Care Centers in Urban Isfahan, Iran - Darani, Firoozeh Mostafavi (2010)
Against the background of increasing proportion of older persons in Iran, a qualitative research with a purpose of exploring the nature of caring behaviors among the elderly at urban health care centers in Isfahan was undertaken. Using a grounded theory approach, the study was guided by three questions: 1) - What is the nature of caring behaviors? 2- What are the conditions that contribute to the present state of caring behaviors?, and 3- What possible intervening conditions may improve the state of caring behaviors? Twenty five elderly respondents, their family members, and health care providers and managers were interviewed in-depth using topics related to issues affecting caring behaviors. Observations, focus group discussions, official documents, and researcher’s field notes and memos formed other sources of the data. The researcher used constant comparative method of data analysis to discover the reality of behaviors of individuals, family members and health care providers, and processes involved. From the data analysis a so-called theory of "Walking a Line between Despair and Hope" had emerged. This theory adequately explains reasons for the elderly’s negative attitude toward the health care system, their family’s barriers in supporting their older parents, and the health care providers’ constraints in delivery of services for the elderly primary health care. As a result of macro and micro conditions (contributing conditions), elderly, their families and health care providers were in reality were making adjustments to what they felt about health care. Despite their desperations at the state of services available, they were hopeful that things would improve. The internal responses included categories depicting ‘accepting conditions as the only way’, ‘feeling of being at the end of the way’, ‘death expectation in spite of potential abilities’, and ‘motivational weakness’. There were also categories that reflected relational-societal processes such as ‘accepting reduction and interruption of communications in old age’, ‘reaction to losing of one's roles’, ‘conformity with others' in order to establish communication’, and ‘accepting others' disinterest to have relations with the elderly’. External responses manifested as behaviors of elderly participants were ‘non-adoption of healthy lifestyle’ and ‘non-adoption of proper caring behaviors’. Internal responses of elderly families consisted of ‘considering the elderly as children’, ‘emotional escape’ and ‘feeling of inability to care’. ‘Pseudo care’ and ‘imperfect care’ were the external responses of elderly families to conditions. Health care providers' internal response included ‘feeling of distress and incapability in offering services’, ‘motivational weaknesses’, ‘considering offering services to the elderly as an additional task’, and ‘compassion and compulsion in offering services’. ‘Perfunctory care’ was manifested as external response of health care providers to conditions. Despite the strong effect of macro and micro conditions on elderly primary health care process, the presence of some factors could be interpreted as signs of despair in some elderly, their families and health care providers. Nevertheless, there were intervening factors such as ‘reinforcing factors’, ‘individuals' characteristics’, ‘perceived concepts of health’, and ‘adaptation mechanisms’ that acted to either mitigate the negative state or influence a positive orientation. This qualitative study has gathered data that could be used by policy makers and health care providers and researchers concerned with elderly health and their quality of life. Particularly for researchers, this study can be used to develop theories on elderly primary health care.